FERTILIZER GIVING EFFECT OF BIOLOGICAL AND CALCIUM ON THE GROWTH AND PRODUCTION PLANT BEAN (Phaseolus vulgaris L.) - Indra Rohman Mutaqin; Oktavianus Lumban Tobing; Nur Rochman (Universitas Djuanda Bogor, 2017)
This study aims to obtain a doses of biological fertilizer and calcium doses that gives the best effect on the growth and production of beans (Phaseolus vulgaris L.) upright type. This experiment was carried out from February until April 2014, at the experimental field of Depatment of Agrotechnology, University of Djuanda Bogor. The experimental design used is a factorial completely randomized design with 5x3 treatments and 3 replications. The first factor biofertilizers (rich bio), A0: control (without biofertilizer), A1: Biological Fertilizer doses of 10 kg / ha, A2: biological fertilizer doses of 20 kg / ha, A3: biological fertilizer dose of 30 kg / ha, A4: microbial doses (as recommended), while the second factor doses of dolomite (CaMg (CO3) 2) consists of: B0: 0 ton / ha (without calcium), B1: 2 tons / ha, B2: 4 tons / ha. The results showed a doses of calcium 4 tons / ha showed a better response in plant height (2 weeks after plant) and the weight of the third harvest pod. Provision of calcium which is accompanied by adequate dosage of biological fertilizer can increase the wet weight and dry weight of stover. Keywords: bean seed upright type, dosage biological fertilizer, calcium